Tonel: Teaterikalitas Pascakolonial Masyarakat Tansi Sawahlunto - Dede Pramayoza (Jurnal Kajian Seni, 2016)
Tonel is a dramatic performing arts that has been living in Tansi Society, Sawahlunto,Sumatera Barat. This study is a preliminary review of the tonel existence in the presenttime that related to the history of Sawahlunto as a colonialization effect. This research usedescriptive analysis of study literature and interview, the description is directed to explore thepostcolonial indication contained in tonel staging practices. The results answered that tonelis a part of a hybrid product in creoles culture, as the effects of colonial policy in the past.In other hand, the study also explained that through theatricality of tonel had an impectedfor Tansi society of Sawahlunto to create a new cultural identity as “Slunto Peoples”